Prevalence of Tobacco Smoking and Its Association With Disease Severity Among Patients With Psoriasis in China: A Cross-Sectional Study - Wei, Lei; Chen, Siting; Zhang, Zhan; Kuai, Le; Zhang, Rui; Yu, Ning; Shi, Yuling; Li, Bin; Wang, Ruiping (Frontiers in Medicine, 2022)
Introduction: Tobacco smoking is associated with the prevalence and severity of psoriasis, and understanding tobacco smoking prevalence among psoriasis patients is critical due to its heavy diseases burden in China. But evidence on the association with psoriasis severity is still limited in China. Objectives: To examine the prevalence of tobacco smoking and explore the association between tobacco smoking and diseases severity among psoriasis patients. Methods: 4,529 psoriasis patients in 200 selected hospitals were recruited in China from January 2020 to September 2021. Detailed information covering demographic feature, tobacco smoking and psoriasis history were collected through an electronic questionnaire, and clinical data was extracted from the HIS (Health Information System). SAS 9.4 was performed for data analysis, and a p-value of less than 0.05 was considered as statistically significant. Results: The prevalence of tobacco smoking was 30.8%, with 24.6% for current smoking. The average PASI (Psoriasis Area and Severity Index) score for psoriasis patients was 9.4, with male patients had higher PASI score than females. The odds ratio (OR) of former tobacco smoking prevalence was 1.5 (95% confidence interval (CI): [1.0-2.3]) for PASI score (3.0-7.0), 2.2 for PASI score (7.1-13.0) and 4.2 for PASI score>13,when compared with patients with PASI score<3.0. Similarly, the OR of current tobacco smoking prevalence was 1.8 (95% CI: [1.5-2.2]) for PASI score (3.0-7.0), 1.9 for PASI score (7.1-13.0), and 3.1 for PASI score>13, when compared with patients with PASI score<3.0. Scatter plots indicated that both of tobacco smoking intensity and smoking duration were positively correlated with psoriasis severity (P<0.05). Conclusions: The prevalence of tobacco smoking was high, especially among male psoriasis patients and those with senior high education. Tobacco smoking was positively associated with psoriasis severity, moreover, both of smoking intensity and smoking duration were positively correlated with the severity of psoriasis in a dose-dependent fashion.